An Analysis of Multi-objective Fuzzy Stochastic Nonlinear Programming Models - Beaula, Thangaraj; Seetha, R. (Communications in Mathematics and Applications, 2022)
A novel method is developed for multi-objective fuzzy stochastic nonlinear programming models with some stochastic constraints in which randomness is described by gamma random variables and fuzziness is expressed by L-R fuzzy numbers. The solution for aforesaid model is obtained by three stages: Defuzzification, conversion of MOSNLPP into MONLLP using chance constrained technique and solving multi objective deterministic nonlinear programming problem. An example is exemplified to validate and strengthen the efficacy of proposed technique.